2021
DOI: 10.35965/jbm.v3i1.590
|View full text |Cite
|
Sign up to set email alerts
|

Pengaruh Saluran Distribusi, Biaya Pemasaran Dan Volume Penjualan Terhadap Pendapatan Petani Kentang Di Kabupaten Gowa Sulawesi Selatan

Abstract: Penelitian ini bertujuan untuk mengetahui berapa besar pengaruh variable saluran distribusi (X1), biaya pemasaran (X2) dan volume penjulan (X3) terhadap pendapatan petani kentan (Y). Dan tujuan berikutnya adalah untuk mengetahui saluran distribusi pemasaran yang paling efisien dari petani hingga ke konsumen akhir. Metode penelitian yang digunakan adalah metode survey dengan menggunakan 143 responden petani kentan yang ada dilokasi peneklitian. Hasil penelitian menunjukkan bahwa variable biaya pemasaran (X2) ku… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
2
4
0
1
Order By: Relevance
“…Distance poses a significant challenge for culinary MSMEs in Jakarta when it comes to Previous research has shown that distribution channels positively impact on business development and income. This is supported by studies conducted by Hasanuddin et al (2020), Anggraini (2018), and Kharisma et al (2020). Based on this description, a sixth hypothesis is described.…”
Section: Impact Of Distribution Channels On the Growth Of Msmes Via B...supporting
confidence: 61%
See 3 more Smart Citations
“…Distance poses a significant challenge for culinary MSMEs in Jakarta when it comes to Previous research has shown that distribution channels positively impact on business development and income. This is supported by studies conducted by Hasanuddin et al (2020), Anggraini (2018), and Kharisma et al (2020). Based on this description, a sixth hypothesis is described.…”
Section: Impact Of Distribution Channels On the Growth Of Msmes Via B...supporting
confidence: 61%
“…Distribution obstacles can profoundly affect the entire business system (Kho, 2019). Previous research has shown that distribution channels have a positive impact on business income, as evidenced by studies conducted by Hasanuddin et al (2020), Anggraini (2018), Greene & Welch (2018), Lee & Lin (2018), Guellec & Paunov (2017), Kharisma et al (2020), Xing et al (2020), and Siregar et al (2020. Given the information provided, the following initial hypothesis is formulated: Hypothesis 1: Distribution channels have a beneficial impact on the income of MSMEs.…”
Section: Impact Of Distribution Channels On Msme Revenuementioning
confidence: 97%
See 2 more Smart Citations
“…Biaya pemasaran adalah biaya yang dikeluarkan untuk memasarkan atau mendistribusikan produk dari produsen ke konsumen akhir (Hasanuddin, 2020). Besarnya biaya pemasaran berbeda antar lembaga pemasaran.…”
Section: Biaya Pemasaranunclassified